The Relationships Among Aging Stereotypes, Aging Anxiety, Social Support, Religiosity, and Expected Health Among Colombians (2019)
The population of older adults is rapidly increasing throughout the world, particularly in Latin American countries. This increase makes it imperative to examine psychosocial perceptions and expectations of aging among these populations, which to date have received little research attention. This study aims to test two models of the associations among psychosocial perceptions, expectations of aging, and religiosity among 544 individuals (52.4% female) whose age ranged from 18 to 59 years (M = 31.7) living in Bogota, Colombia. The first model examines associations among psychosocial perceptions and psychosocial aging outcomes, while the second examines associations between these constructs and religiosity. The first model indicates that three major psychosocial predictors (social support, positive and negative aging stereotypes) are uniquely associated with three psychosocial aging outcomes (expected aging-related support, aging anxiety, expected health). The second model indicates that higher religiosity is associated with higher perceived current social support and expected aging-related support, greater endorsement of positive aging stereotypes, and lower reported aging anxiety. Results extend the literature on psychosocial perceptions and expectations of aging to Colombia and suggest that religiosity may play an important role in shaping psychosocial expectations and perceptions of aging in Colombia. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.